Faktor-Faktor Yang Berhubungan Dengan Kepatuhan Berobat Pasien Tuberkulosis Paru di Lima Puskesmas di Kota Manado - Kondoy, Priska P.H.; Rombot, Dina V.; Palandeng, Henry M.F.; Pakasi, Trevino A. (UNIVERSITAS SAM RATULANGI, 2014)
Based on Global Tuberculosis Control WHO 2012, Indonesia went up from fifth to forth rank after India, China, and South Africa, obviously problem within restraint of Tuberculosis has increased. On 2008 North Sulawesi classified Pulmonary TB diseases as the top 10 infectious diseases with a prominent number of 1,571 cases. Manado City on 2012 Pulmonary Tuberculosis with BTA positive number was 1.645 cases. Basically, this condition exhibit an efforts development of healthy in order to improve risk factors for Pulmonary TB until now has not been entirely successful. The type of this research is cross sectional that purpose to know risk of factors (age, gender, education, employment, level of income, knowledge and the side effects of anti-tuberculosis drugs related with obedience of treatment pa-tients with Pulmonary Tuberculosis in five health centers in the city of Manado. There were 171 samples taken from a total population of 119 people. Data obtained from direct interviews using questionnaires. The statistical test used was Chi square. The result of research indicates that the variable, which relates with treatment compliance of TB pa-tient, is education. (p=0,000) and knowledge (p=0,000). Variable that are not related to obedience of treatment TB patients are age, gender, education, occupation, level of income and side effect OAT (p=0,05).Keywords: Clean and Health Behaviour, Knowledge, Attitude and Behaviour